2021
DOI: 10.1093/neuros/nyaa563
|View full text |Cite
|
Sign up to set email alerts
|

Encephaloduroarteriosynangiosis Averts Stroke in Atherosclerotic Patients With Border-Zone Infarct: Post Hoc Analysis From a Performance Criterion Phase II Trial

Abstract: BACKGROUND Intracranial atherosclerotic disease (ICAD) is one of the leading causes of stroke worldwide. Patients with ICAD who initially present with ischemia in border-zone areas and undergo intensive medical management (IMM) have the highest recurrence rates (37% at 1 yr) because of association with hemodynamic failure and poor collaterals. OBJECTIVE To evaluate the effect of encephaloduroarteriosynagiosis (EDAS) on stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Although the EDAS technique has been described several times in the literature, no reports have evaluated the multidisciplinary approach to improve operative outcomes and the effects of maintaining strict medical management in patients at high risk of recurrent stroke. As the role of EDAS potentially expands to treat conditions such as ICAD, 3,5,7,21 it is necessary to identify the detailed nuances and variables that can be controlled to ensure good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the EDAS technique has been described several times in the literature, no reports have evaluated the multidisciplinary approach to improve operative outcomes and the effects of maintaining strict medical management in patients at high risk of recurrent stroke. As the role of EDAS potentially expands to treat conditions such as ICAD, 3,5,7,21 it is necessary to identify the detailed nuances and variables that can be controlled to ensure good outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…66 Finally, data from the ERSIAS study (Surgical Indirect Revascularization for Symptomatic Intracranial Arterial Stenosis) showed that in patients with symptomatic ICAD and border zone infarction, encephalo-duro-arterio-synangiosis seems to be safe with 10.7% recurrent stroke at 24 months. 67 Due to safety concerns with angioplasty/stenting, current guidelines 19 and the FDA recommend against its use as a first-line treatment for patients with ICAD; thus, it is currently considered only in those who had 2 or more strokes despite optimal medical treatment. 64 Identifying a subgroup of ICAD patients risk stratified using biomarkers of impaired distal blood flow/perfusion and whose 90-day recurrent stroke is higher than that of stenting may help identify a high-risk group of patients with ICAD with a high recurrent stroke risk despite optimal medical treatment.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…The rates of early stroke were also nominally lower than in previous studies of direct bypass and angioplasty/stenting, reaching the prespecified threshold set for advancement to phase III study. 59,83 An additional prospective comparative study of EDAS in intracranial atherosclerotic disease resulting in MCA occlusion by Zhang et al 58 also showed a nominal reduction in rates of stroke and death with EDAS, although this effect did not reach statistical significance due to the limited sample size.…”
Section: Surgical Strategiesmentioning
confidence: 99%